Brucio nel vento: Silvio Soldini’s ’fiery’ adaptation of Agota Kristof’s Hier - Luciano, Beernadette (Spunti e Ricerche, 2016)
The connection between literature and cinema is decidedly and consciously different in Soldini’s 2001 film Brucio nel vento, the only instance in which Soldini deviates from an original screenplay and attempts an acknowledged adaptation of a literary text. In my analysis of Soldini’s film, I examine textual, thematic and extra-diegetic elements central to his "re-creation". I explore Soldini’s self-conscious "translation" of the literary code into the cinematic code. I consider how Soldini’s treatment of the novel’s central theme aligns itself with a post-modern and feminist reading of mobility and nomadism. Finally I consider an extra-diegetic element, that I call authorial sympathy.